On the irremovability of mathematical subject - Olszewski, Adam (Philosophical Problems in Science (Zagadnienia Filozoficzne w Nauce), 2010)
In the paper the author attempts to show that the Mathematical Subject is irremovable from the Philosophy of Mathematics. In doing so he wants to argue, first, that Church’s Thesis should be seen as a statement about the Mathematical Subject. Second, he wants to show that philosophical relations between some problems such as Koenig’s lemma vs Fan theorem, or Goedel’s theorem on incompleteness vs. Halting problem, could be better grasped within the framework of the Mathematical Subject.